First, let's simplify the given equations:
1) 7x + 3 = 7x + 3: There's no need to change this equation.
2) 3(4x + 8) = 4(3x + 6): Expand both sides to get 12x + 24 = 12x + 24.
Now we can plug in different values of 'x' and see if they give the same result.
Let's try x = 1:
1) 7(1) + 3 = 7(1) + 3: 10 = 10, which is true.
2) 12(1) + 24 = 12(1) + 24: 36 = 36, which is also true.
Let's try x = 2:
1) 7(2) + 3 = 7(2) + 3: 17 = 17, which is true.
2) 12(2) + 24 = 12(2) + 24: 48 = 48, which is also true.
As we can see from these examples, plugging in different values of 'x' results in the same values for both equations. This means that both equations have more than one solution. In fact, both equations are actually the same equation because they have the same form, and therefore have infinitely many solutions for any value of 'x'.
7x+3=7x+3 3(4x+8)=4(3x+6)
Plug more than one point into the original equations and check to show that the equations can have more than one solution. Explain your work.
1 answer